Arsenic in the water and agricultural crop production system: Bangladesh perspectives - Arifin Sandhi; Changxun Yu; Md Marufur Rahman; Md. Nurul Amin (Environmental Science and Pollution Research, 2022)
The presence of high levels of carcinogenic metalloid arsenic (As) in the groundwater system of Bangladesh has been considered as one of the major environmental disasters in this region. Many parts of Bangladesh have extensively reported the presence of high levels of arsenic in the groundwater due to both geological and anthropogenic activities. In this paper, we reviewed the available literature and scientific information regarding arsenic pollution in Bangladesh, including arsenic chemistry and occurrences. Along with using As-rich groundwater as a drinking-water source, the agricultural activities and especially irrigation have greatly depended on the groundwater resources in this region due to high water demands for ensuring food security. A number of investigations in Bangladesh have shown that high arsenic content in both soil and groundwater may result in high levels of arsenic accumulation in different plants, including cereals and vegetables. This review provides information regarding arsenic accumulation in major rice varieties, soil-groundwater-rice arsenic interaction, and past arsenic policies and plans, as well as previously implemented arsenic mitigation options for both drinking and irrigation water systems in Bangladesh. In conclusion, this review highlights the importance and necessity for more in-depth studies as well as more effective arsenic mitigation action plans to reduce arsenic incorporation in the food chain of Bangladesh.